Efficient implementation of accurate geometric transformations for 2-D and 3-D image processing - Dooley, Saul R (IEEE transactions on image processing : a publication of the IEEE Signal Processing Society, 2004)
This paper proposes the use of a polynomial interpolator structure (based on Horner's scheme) which is efficiently realizable in hardware, for high-quality geometric transformation of two- and three-dimensional images. Polynomial-based interpolators such as cubic B-splines and optimal interpolators of shortest support are shown to be exactly implementable in the Horner structure framework. This structure suggests a hardware/software partition which can lead to efficient implementations for multidimensional interpolation